Acceptability, feasibility, and utility of a safety aid reduction treatment in underserved veterans: a pilot investigation. Issue 1 (2nd January 2023) - Raines, Amanda M.; Chambliss, Jessica L.; Norr, Aaron M.; Sanders, Natalie; Smith, Shawn; Walton, Jessica L.; True, Gala; Franklin, C. Laurel; Schmidt, Norman B.
ABSTRACT: Access to mental health services, particularly for veterans residing in underserved communities, remain scarce. One approach to addressing availability barriers is through the use of group-based transdiagnostic or unified treatment protocols. One such protocol, Safety Aid Reduction Treatment (START), previously termed False Safety Behavior Elimination Treatment (FSET), has received increasing empirical support. However, prior research has only examined this treatment among civilians with a primary anxiety diagnosis. Thus, the purpose of the current study was to replicate and extend prior research by examining the acceptability, feasibility, and utility of START among veterans, particularly those living in underserved communities, and across a wider array of diagnoses. Veterans ( n  = 22) were assessed prior to, immediately after, and one month following the 8-week treatment. The majority of veterans found START useful and acceptable. Additionally, recruitment and retention rates suggest that the treatment was feasible. Notably, results revealed reductions in overall anxiety, depression, and safety aid usage, which were maintained throughout the brief follow-up period. These findings add to a growing body of literature highlighting the utility of transdiagnostic approaches in the amelioration of various anxiety and related disorders. Limitations include the small sample size and uncontrolled design.